2012
DOI: 10.1148/radiol.12111459
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Nodule Size Evaluation with Chest Tomosynthesis

Abstract: Measurements on chest tomosynthesis and CT images are comparable, because there is no evident bias between the modalities and the repeatability is similar. The LOA between measurements for the two modalities raise concern if measurements from chest tomosynthesis and CT were to be used interchangeably.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 20 publications
4
20
0
Order By: Relevance
“…9 Several TOMO phantom studies have reported limited underestimation of the actual size, whereas studies using CT have found underestimated or overestimated nodule sizes. 7,10,11 In the present study, both modalities underestimated the diameters of phantom nodules. TOMO appeared to slightly underestimate the nodule size (mean measurement error, 20.84 mm); however, such an error is clinically relevant because nodule management is based on an absolute nodule size threshold.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…9 Several TOMO phantom studies have reported limited underestimation of the actual size, whereas studies using CT have found underestimated or overestimated nodule sizes. 7,10,11 In the present study, both modalities underestimated the diameters of phantom nodules. TOMO appeared to slightly underestimate the nodule size (mean measurement error, 20.84 mm); however, such an error is clinically relevant because nodule management is based on an absolute nodule size threshold.…”
Section: Discussionsupporting
confidence: 51%
“…Recently, underestimation of nodule size associated with manual measurement of clinical nodules on TOMO has been reported. 7 Svahn et al 16 found that the extent of in-plane artefacts varied linearly with the spherical diameter and relative contrast of Regarding repeatability, the interobserver 95% LOA for measuring TOMO diameters by the pair of radiologists who recorded the most similar results was 20.06 to 0.83 mm, the values were similar to the CT data. These values were slightly less than the variation of 21.3 to 1.5 mm in the measurement of clinical nodules reported by Johnsson et al 7 in 2012.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…follow-up of pulmonary nodules. [22][23][24] Finally, owing to the very low dose of DTS, it has been suggested as a suitable technique for lung cancer screening. 25 Three DTS systems for chest tomosynthesis currently exist.…”
Section: Introductionmentioning
confidence: 99%
“…igital tomosynthesis has been applied to a variety of applications, including breast imaging (1-3), orthopedic imaging (4-8), urologic imaging (9), and chest imaging (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Digital chest tomosynthesis has been available and cleared by the U.S. Food and Drug Administration since 2006.…”
mentioning
confidence: 99%